SOCIOECONOMIC INDICATORS: AN ANALYSIS FROM THE PERSPECTIVE OF THE SOCIAL VULNERABILITY INDEX - Pereira da Silva Leão, Airton; Samelyne Lima da Silva, Layza; Melo Costa Simões, Valéria (Revista Gênero e Interdisciplinaridade, 2026)
The objective of this article is to analyze the income and employment indicator in the municipality of Açailândia, Maranhão, using data reported by the Social Vulnerability Index between 2000 and 2010. The concept of social vulnerability has been used to characterize a segment of the population that is in an unfavorable situation compared to other population groups. The Income and Employment dimension of this study incorporates the following indicators: percentage of households with per capita household income equal to or less than half the minimum wage in 2010, adult unemployment rate, informal employment of adults with low levels of education, income dependence of elderly people, and the presence of child labor. The results found in this research suggest that the theme of social vulnerability represents a recent research topic of growing interest in scientific production.